2019
DOI: 10.5964/ejop.v15i4.1921
|View full text |Cite
|
Sign up to set email alerts
|

The illusion of knowing in college: A field study of students with a teacher-centered educational past

Abstract: In the present study, the tendency to overestimate performance (illusion of knowing) was examined in college students whose educational past experiences had emphasized verbatim learning. Female students enrolled in core curriculum classes were sampled. Classes taught by the same instructor were randomly assigned to a self-assessment practice condition, where students predicted their test and class performance and were asked to reflect on discrepancies between predictions and actual performance, or to a control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Avhustiuk et al (2018) found that students' general self-efficacy increased with the accuracy of self-assessment, whereas Hamann et al (2020) reported that it contributed to inaccuracies of self-assessment and to the confidence with which students made estimates. In the Middle East, Al and Pilotti et al (2019) reported no relationship between general selfefficacy and estimation accuracy or confidence. However, Pilotti et al (2019) found that general-self-efficacy contributed to test grades, suggesting that it may motivate behavior rather than regulate behavior via metacognition.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Avhustiuk et al (2018) found that students' general self-efficacy increased with the accuracy of self-assessment, whereas Hamann et al (2020) reported that it contributed to inaccuracies of self-assessment and to the confidence with which students made estimates. In the Middle East, Al and Pilotti et al (2019) reported no relationship between general selfefficacy and estimation accuracy or confidence. However, Pilotti et al (2019) found that general-self-efficacy contributed to test grades, suggesting that it may motivate behavior rather than regulate behavior via metacognition.…”
Section: Introductionmentioning
confidence: 88%
“…In the Middle East, Al and Pilotti et al (2019) reported no relationship between general selfefficacy and estimation accuracy or confidence. However, Pilotti et al (2019) found that general-self-efficacy contributed to test grades, suggesting that it may motivate behavior rather than regulate behavior via metacognition. These inconsistencies demand further examination.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations